Intensification of the Prices Volatility for Oil and Natural Gas - PETRE PRISECARU; PAUL CALANTER (Global Economic Observer)
Energy prices are generally more volatile than the prices of other commodities. This is because shortterm energy demand responds more quickly to the impact of economic growth than to price changes. This paper aims to analyse this phenomenon. Therefore, when an energy shock occurs, an important price change may be necessary to influence the market. Currently such shock has been caused by the COVID-19 pandemic, which has produced the biggest sustained change in demand since World War II. In the medium to long term, energy prices will rise if investment will not be on an upward trend, which seems unlikely given the current environmental protection guidelines adopted by many countries around the world. In our paper we argue that supply and demand shocks and high price volatility are likely to continue to weigh on the energy market and the global economy.